(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article deals with the role of professional orientation in teaching foreign at non-filological faculties. The author pays attention to the importance of educational process adaptation to the specific professional areas of students and offers methodological approaches to the development of professional communicative competence.